Dampak Labelling Terhadap Mantan Narapidana Narkotika ( Studi Kasus Remaja Di kecamatan Ujung Batu, Kabupaten Rokan Hulu) - ALROBI DIPAPOLANDA , ALROBI DIPAPOLANDA; Syahrul Akmal Latif, (Sisi Lain Realita, 2023)
Labeling former drug convicts can have significant impacts on various aspects of their lives. This study aims to examine the impacts of labeling on former drug convicts, particularly adolescents in the Ujung Batu District, Rokan Hulu Regency. The research method used is qualitative with a descriptive approach to understand the phenomenon experienced by the research subjects holistically. Data were obtained through interviews and observations of informants selected based on their understanding of the researched issues. The results show that labeling former drug convicts can have negative impacts on adolescents, such as stigmatization, discrimination, and difficulties in obtaining employment or further education. The research location was chosen based on the presence of research objects, namely adolescents in the area. The researcher also expresses gratitude to various parties who have assisted in completing this thesis, including supervisors, family, and friends. The conclusion of this study emphasizes the importance of society's understanding of the impacts of labeling on former drug convicts so that involved adolescents can have fair and decent opportunities in social life.